Meningkatkan Aktivitas Belajar PPKN Di Kelas 5 Menggunakan Model PBL, GI Dan TGT - St. Rahmatul Hidayah; Khairil Anwar (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This type of research is a Classroom Action Research (PTK), which is carried out in three meetings. The research subjects were grade V even semester students of UPTD SDN Panggung Baru in the academic year 2022/2023 with a total of 10 students. The type of data in this research is qualitative and quantitative data. Qualitative data were obtained through observation of teacher activities, student activities and learning discipline questionnaires. Quantitative data were obtained through individual written test techniques. Analysis of the data in this study using descriptive analysis techniques and cross tabulation described by tables, graphs and interpretation by percentage.The results of this study indicate that the teacher's activity at the meeting 1 is quite good, the meeting 2 is good, and the meeting 3 is very good. Student activity at meeting 1 was quite active, meeting 2 was active, and meeting 3 was very active. Student learning discipline in meeting 1 was quite disciplined, meeting 2 was disciplined, and meeting 3 was very disciplined, with each meeting experiencing an increase. Classical completeness of student learning outcomes at meeting 1 reached 50%, meeting 2 reached 80%, and 3 reached 100%. Based on these findings it can be concluded that the Problem based learning, Group Investigation and Teams Games Tournament Learning Model can increase student activity, discipline and learning outcomes.